Pengaruh Perendaman Air Laut Terhadap Sifat Mekanik pada Hasil Pengelasan Plat St 37 pada Lambung Kn. Ae-012 Distrik Navigasi Kelas Iii Pontianak - Joni Rahmadi; Fuazen; Eko Julianto; Hasanudin (Syntax Literate, 2023)
In the current era of industrialization, welding techniques have been widely used, covering the work of shipping, bridges, steel frames, pipelines and so on, although this is not the main objective, it is a means to achieve a better manufacturing process. so you have to really pay attention to the suitability between the properties of the welding itself, namely the strength of the connection and pay attention to the connection to be welded, so that the results of the welding are as expected. Welding applications include shipyard construction in the framework of making bodies and other parts, so it is necessary to pay attention to the relationship to the corrosion rate that occurs at welding joints. Seawater intrusion on steel construction corrodes the structure due to the content of chloride and sulfate ions in seawater which react to the chemical elements of the steel. So that the corrosion rate that occurs greatly affects the mechanical properties of the ST 37 plate welding results on the KN hull. AE-012 Pontianak Class III Navigation District, on tensile strength and bending strength in the workpiece, HAZ area, and base metal. Testing the strength of the welding joints with Electric Arc Welding using a current strength of 120 Amperes on mild steel material (ST 37) against the effect of salt water immersion for 20 days, 35 days and 50 days the following values are obtained: [i] At 20 days of immersion time the value the tensile strength is 202.08 N/mm2 , 35 days the tensile strength value is 215.42 N/mm2 and 50 days the tensile strength value is 221.46 N/mm2 , [ii] For the tensile strength values at immersion of 35 days and 50 days has a value that tends to increase, this is somewhat different from the value of the tensile strength at 20 days immersion time which tends to decrease the value of the tensile strength without immersion. The effect of salt water immersion on the value of bending strength in mild steel (ST 37), it was found that: [i] At 20 days of immersion the bending strength value was 1500 N/mm2, 35 days the bending strength value was 1845 N/mm2 and 50 days the bending strength value was the bending strength is 1460 N/mm2 , [ii] The bending strength value at 35 days immersion has a value that tends to increase closer to the bending strength value without immersion, this is somewhat different from the bending strength value at 50 days immersion which tends to decrease considerably at compare without immersion.